Dry-land lower limb strength and power are related to start and tumble turn performance in young sub-elite swimmers - Forsyth, J. R.; Steele, J. R. (Journal of Australian Strength and Conditioning, 2020)
This study aimed to investigate differences in swimming performance and dry-land characteristics of higher and lower performing young swimmers, as well as identify any associations between swim and dry-land performance. Sixteen young, competitive swimmers (8 males; age 15.6±1.7 years, height 175.6±9.5 cm, mass 63.5±10.1 kg) who had qualified for their National Championships were recruited. Swimmers undertook simulated 100 m freestyle sprints where their starts, turns and velocities were recorded. Additionally, strength and power were assessed in an isometric mid-thigh pull (IMTP), squat jump (SJ) and countermovement jump (CMJ). The cohort was then split into two groups, those who made the finals (n=9) and those who did not (n=7), and independent samples t-tests were used to determine whether there were any differences in swim and dry-land performance. Similarly, Pearson product-moment correlation coefficients were calculated between these performance metrics to identify any significant relationships. On average, the participants` highest FINA points (p=0.001) and total turn time (p=0.044) were significantly different between the two groups; however, no further differences were found between the participants` start and turn performances. Group differences were shown in dry-land performances such as IMTP relative peak force (p=0.017) and CMJ relative peak power (p=0.017). Correlations were also found between the swim and dry-land performances, including the participants` best results at Nationals and CMJ relative net impulse (r=0.758, p=0.001), as well as dive length and CMJ jump height (r=0.759, p=0.001). The results suggest that these trainable dry-land characteristics should be emphasised through resistance training as young swimmers approach competition to ensure they can perform at a high level.